Putting the Indices into practice: censoring science in early modern Portugal. - Malta Romeiras, Francisco (Annals of Science, 2020)
During the sixteenth and seventeenth centuries, the Inquisition was the institution most invested in the censorship of printed books in the Portuguese empire. Besides publishing the Indices of Forbidden Books, the Holy Office was also responsible for overseeing their implementation and ensuring their efficacy in preventing the importation, reading, and circulation of banned books. Overall, the sixteenth-century Indices condemned 785 authors and 1081 titles, including 52 authors and 85 titles of medicine, natural history, natural philosophy, astronomy, chronology, cosmography, astrology, and divinatory arts. By looking at the largest collection of early modern scientific books in Portugal, I will argue that a closer inspection of marginalia and ownership, and the establishment of a typology of expurgations is essential for the comprehension of the actual practices and the mechanisms of censorship. By examining the material evidence of censorship, in order to reconstruct expurgation practices, this paper reveals the processes and effectiveness of ecclesiastical control in the Portuguese Inquisition and highlights the differences between what inquisitors wrote in the Indices and what others put into practice.